Volyn tragedy in cinema and theatre - Oksana Kalishchuk (Cхід, 2019)
Cinema is rightly considered as a powerful socio-communicative channel of information space. Its significance is strengthened in a case of appealing to the ticklish topic. An overview of works of cinema and theater art devoted to the Ukrainian-Polish conflict in the years of World War II on the West of Ukraine are proposed in article. The attention is paid not only to the plot variety of the films, but also to the philosophical, hermeneutical, psychoanalytic opportunities and the requirement of their thorough study. Thus, an accent on the individualization of the Volhynian events through the person of witnesses, people who survived it, has become specific in particular to the chronicle-documentary and popular science-fiction films. The feature of documentary films about Volyn’43 is the inability to make them more aesthetic and distant. The ability to cause emotional empathy should be considered the main task of both cinematography and theater at the present stage. Today, cinema and theatre works are the elements of national self-identification and the formation of national memory. Documentary and especially feature films can restore and reinforce old stereotypes and create new myths. The more than seventy-years-old experience is becoming an experience of contemporaries through the means of modern art. It is concluded that both documentary and featured films and theatrical performances are one of the ways of international dialogue. Intensive discussions that are prompted in Ukrainian and Polish societies by such feature films as “Volyn” by Wojciech Smarzowski are the bright demonstration of its over-significance. At the same time, it should be understood that it is important to talk about topics that are painful to the society.